Personal Hygiene and Toxoplasmosis Occurences in "Bungkul Cat Lovers” Cat Owners Community in Surabaya: An Association Study - Irma Rachmawati (JURNAL KESEHATAN LINGKUNGAN, 2019)
Pet owners, especially those often in contact with cats, are susceptible to Toxoplasma gondii infection. Personal hygiene is a control for various kinds of disease, one of which is Toxoplasmosis. The aim of this research was to analyze correlation between cat exposure and personal hygiene habits which consist of handwashing, using personal protective equipment and cleaning residents with toxoplasmosis. This research used cross sectional design with a sample size of 19 respondents, which was determined according to the simple random sampling technique. The research was done on the "Bungkul Cat Lovers" cat owners community 2018 in Surabaya. Data were analyzed using Fisher's exact test. Data were collected through Anti-Toxoplasma IgG and IgM Immunoglobulins laboratory tests, interviews, questionnaires and observations. Serologic test results showed that positive Anti-Toxoplasma IgMs were 0% and positive Anti-Toxoplasma IgGs were 31,4%. The result showed that there was a correlation between personal hygiene habits which consist of handwashing (p=0,041<0,05), using personal protective equipment (p=0,044<0,05) and cleaning residents with Toxoplasmosis (p=0,018<0,05). The conclusion of this research is that personal hygiene holds an important role in Toxoplasmosis.